Ten Minutes of α-tACS and Ambient Illumination Independently Modulate EEG α-Power - Stecher, Heiko I.; Pollok, Tania M.; Strüber, Daniel; Sobotka, Fabian; Herrmann, Christoph S. (Frontiers in Human Neuroscience, 2017)
Transcranial alternating current stimulation (tACS) sees increased use in neurosciences as a tool for the exploration of brain oscillations. It has been shown that tACS stimulation in specific frequency bands can result in aftereffects of modulated oscillatory brain activity that persist after the stimulation has ended. The general relationship between persistency of the effect and duration of stimulation is sparsely investigated but previous research has shown that the occurrence of tACS aftereffects depends on the brain state before and during stimulation. Early alpha neurofeedback research suggests that particularly in the alpha band the responsiveness to a manipulation depends on the ambient illumination during measurement. Therefore, in the present study we assessed the brain’s susceptibility to tACS at the individual alpha frequency (IAF) during darkness compared to ambient illumination. We measured alpha power after 10 min of stimulation in 30 participants while they continuously performed a visual vigilance task. Our results show that immediately after stimulation, the alpha power in the illumination condition for both the stimulated and sham group has increased by only about 7%, compared to about 20% in both groups in the ‘dark’ condition. For the group that did not receive stimulation, the power in darkness remained stable after stimulation, whereas the power in light increases by an additional 10% during the next 30 min. For the group that did receive stimulation, alpha power during these 30 min increased by another 11% in light and 22% in darkness. Since alpha power already increases by about 10% without stimulation, the effect of illumination does not seem to interact with the effect of stimulation. Instead, both effects seem to add up linearly. Although our findings do not show that illumination-induced differences in oscillatory activity influence the susceptibility towards tACS, they stress the importance of controlling for factors like ambient light that might add an independent increase or decrease to the power of brain oscillations during periods, where possible persistent effects of stimulation are explored.